Dental Caries Prevalence among 3 - 14 Year Old School Children of Chitwan - Adhikari, Santosh; Tamrakar, Lucky; Humagain, Manoj; Bhattarai, Rosina (Journal of Nepalese Association of Pediatric Dentistry, 2021)
Introduction: Dental caries, an infectious microbiologic disease of dental hard tissues is a global public health problem. It affects people of all ages with the highest priority risk group being school-going children. Objective: This study was done to assess the prevalence of dental caries in the 3-14 years old school children of Chitwan and to compare it across genders, age groups and school groups. Methods: This was a cross-sectional study conducted from January 2018 to May 2018 where WHO criteria was used to examine and calculate DMFT and dft (decayed filled teeth) indices among 360 school children. Statistical analysis was done with SPSS 20. Statistical significance was determined using independent t-test and ANOVA test. Results: The prevalence of the dental caries was found to be 85.83% with mean DMFT of 3.01 ± 2.24 among school children of Chitwan. Caries prevalence was higher in females compared to males, and in government schools compared to private school. Caries experience was highest in middle childhood group 7-12 years (89.20%, mean “DMFT+dft” 3.56 ± 2.33) followed by late childhood group of 13-14 years (84.72%, mean DMFT 2.68 ± 1.95) and early childhood group of 3-6 years (77.33%, mean dft 1.76 ± 1.60) and the differences were statistically significant. The difference in caries experience between private and government school groups as well as in male and female children was not statistically significant. 82.7% of the children had untreated caries while only 5.83% had filled teeth in their mouth. Conclusions: The prevalence of dental caries was higher in middle childhood group and higher percentage of untreated decays, calls for the need of immediate preventive as well as curative interventions.